The Discharge Preceding the Intense Reillumination in Positive Leader Steps Under the Slow Varying Ambient Electric Field - Shengxin Huang; Weijiang Chen; Zhehao Pei; Zhong Fu; Liufang Wang; Tianyu He; Zhijun Li; Jianwei Gu; Kai Bian; Nianwen Xiang; Yu Wang (Geophysical Research Letters)
Abstract Under the slow varying ambient electric field, positive leader propagation exhibits steps characterized by intense reilluminations and abrupt elongations. These steps are currently not well understood. In this work, we investigate these steps in laboratory atmospheric discharges, using a high‐speed video camera and a synchronized electrical parameter measurement system. The discharge, emitting weak light and preceding the intense reillumination, is discovered. This finding suggests that the leader channel actually restarts and extends forward before the intense reillumination, which deepens our understanding of the dynamic process of the positive leader step. The discharge before the intense reillumination contributes to the corona inception from the electrode, leading to the intense reillumination of the leader channel and the emergence of an intense corona streamer burst from the leader tip.